Electronic device and social network use and sleep outcomes among adolescents: the EHDLA study - Anelise Reis Gaya; Rodolfo Brum; Keith Brites; Adroaldo Gaya; Letícia de Borba Schneiders; Miguel Angelo Duarte Junior; José Francisco López-Gil (BMC, 2023)
Abstract Background Considering the evident risk in the literature between the use of screen devices and sleep, there are still few studies on the relationship between each electronic screen device, media programs and sleep duration and sleep-related problems among adolescents and which variables interfere in these relationships. Therefore, this study has the following objectives: (1) to determine which are the most common electronic display devices related to sleep time and outcomes and (2) to determine which are the most common social network applications, such as Instagram and WhatsApp, associated with sleep outcomes. Methods This was a cross-sectional study with 1101 Spanish adolescents between 12 and 17 years old. Age, sex, sleep, psychosocial health, adherence to the Mediterranean diet (MD), sport practice, and time spent on screen devices were assessed by an ad hoc questionnaire. Linear regression analyses were applied, adjusting for several covariables. Poisson regression was applied between the sexes. A p value < 0.05 was considered statistically significant. Results Cell phone use was more associated with sleep time (13%). In boys, time spent on cell phones (prevalence ratio [PR] = 1.09; p < 0.001) and videogames (PR = 1.08; p = 0.005) had a higher prevalence ratio. When psychosocial health was included in the models, we found the greatest association (Model 2: PR = 1.15; p = 0.007). For girls, time spent on the cell phone was significantly associated with sleep-related problems (PR = 1.12; p < 0.001), and adherence to the MD became the second most important in the model (PR = 1.35; p < 0.001), followed by psychosocial health and cell phone use (PR = 1.24; p = 0.007). Time spent on WhatsApp was associated with sleep-related problems only among girls (PR = 1.31; p = 0.001) and was the most important variable in the model along with MD (PR = 1.26; p = 0.005) and psychosocial health (PR = 1.41; p < 0.001). Conclusions Our results suggest a relationship between cell phones, video games, and social networks with sleep-related problems and time.